A Study on Sustainability Consciousness among Student Teachers - Lahari, Alapati; K., Anil Kumar (JOURNAL OF INDIAN EDUCATION, 2024)
Education plays a central role in sustainable development. In the education system, teachers play a key role in integrating the concepts of sustainable development into their classrooms, thus, developing sustainable citizens. This paper explores sustainability consciousness of student teachers through descriptive survey method. The purpose of the study was to understand the sustainability consciousness of student teachers with respect to different dimensions (environment, social and economic) and constructs (knowingness, attitude and behaviour) of sustainability, and also to understand the differential effect of major subjects of study and gender on sustainability consciousness. The findings of the study reveal that majority of the student teachers have only ‘average level’ of sustainability consciousness and there are differences in the level of consciousness with respect to the various dimensions. This has major implications for the teacher education programmes as the teachers have a major role to play for developing sustainability consciousness among the students for a better tomorrow and also to align with the Sustainable Development Goal 4. The paper concludes with suggestive ways of developing sustainability consciousness among the students through various curricular and non-curricular means.